Stress among teachers in SJK(T) Simpang Lima, Klang - Thesigah, Sooganathan (2019)
Stress refers to the physical, psychological, and behavioural reactions experienced by individuals in situations where they feel they are in danger or being overwhelmed or pushed beyond their abilities or limits. Stress is a major factor that affects the job satisfaction of an individual in the workplace. This research was done to analyse the factors influencing job stress among teachers in SJK(T) Simpang Lima, Klang. The objective of this research is to determine the level of occupational stress based on the identified factors among teachers in the school. The factors are working environment, workload, relationship with colleagues, and role ambiguity among teachers in SJK(T) Simpang Lima, Klang. A total of 106 questionnaires were handed out, and 103 valid questionnaires were returned by the respondents who are teachers at the school. A simple random sampling procedure was used to select the respondents from the school. Data were gathered and analysed using Statistical Package for Social Sciences (SPSS) version 24. Descriptive analysis and inferential statistics were used to identify the relationship between the variables and draw inferences between the independent and dependent variables. All the four variables, namely working environment, workload, relationship with colleagues, and role ambiguity, were found to be significantly correlated with stress among primary school teachers. The research also revealed that the teachers in SJK(T) Simpang Lima, Klang face a moderate level of stress. Regression analysis revealed that the factors explain for 65.4% of the stress experienced by the primary school teachers. Future researchers are recommended to perform qualitative studies using the same variables or different variables within the same or different sector. As a conclusion, stress plays a major role among teachers in SJK(T) Simpang Lima, Klang.